Malaysia highway authority 30 years of developing the highway network - Jacobs, Jennifer (Editions didier Millet, 2011)
The Malaysian Highway Authority has been at the forefront of developing Malaysia's world-class network of toll expressways for more than 30 years. This book reveals the important role plays by the authority and showcases the infrastructure and operations of 29 of the main expressways including three still under construction.